Delegated portfolio management and diversification. Issue 4 (3rd March 2016) - Christensen, Michael; Christensen, Michael Vangsgaard; Gamskjaer, Ken
Abstract: This article analyses the potential diversification benefits available to high-net-worth investors utilizing multiple portfolio managers. We show that enlisting seven actively managed portfolios from multiple portfolio managers generate significant benefits in terms of risk reduction, and, interestingly, diversification benefits are shown to be larger for low-risk portfolios compared to high-risk portfolios.